Progression of coronary atherosclerosis in patients without standard modifiable risk factors - Jawad Mazhar; Gemma Figtree; Stephen T. Vernon; Keyvan Karimi Galougahi; Julie Carlo; Steven E. Nissen; Stephen J. Nicholls (Elsevier, 2020)
Background and aims: The outcome of patients with clinical coronary artery disease despite traditional risk factors is poorly understood. Methods: Clinical characteristics and plaque burden on serial intravascular ultrasonography were compared in patients without (n ​= ​165) and with (n ​= ​492) standard modifiable risk factors after matching on age, sex and use of statins from a database of 5823 patients participating in clinical trials of anti-atherosclerotic therapies. Results: Patients without standard modifiable risk factors had lower baseline systolic blood pressure (118 ​± ​12 vs. 129 ​± ​17 ​mmHg, p ​< ​0.001), low-density lipoprotein cholesterol (87 ​± ​21 vs. 104 ​± ​34 ​mg/dl, p ​< ​0.001), triglycerides [106 vs. 136 ​mg/dl, p ​< ​0.001)] and C-reactive protein [1.5 vs. 2.1 ​mg/l, p ​= ​0.001]. At baseline, patients without modifiable risk factors had a lower percent atheroma volume (35.7 ​± ​8.6 vs. 38 ​± ​8.8%, p ​= ​0.004) and total atheroma volume (174.7 ​± ​80 vs. 190.9 ​± ​84 ​mm3, p ​= ​0.03) and less images with calcification (22.2 vs. 26.5%, p ​= ​0.025). The use of aspirin and statin prior to and during the trials was similar. The use of ACE inhibitors and beta blockers was lower in the no risk factor group prior to and during the trials. The change in percent atheroma volume (−0.2 ​± ​2.8 vs. −0.1 ​± ​3.6%, p ​= ​0.71), total atheroma volume (−5.5 ​± ​23.4 vs. −3.8 ​± ​22.7 ​mm3, p ​= ​0.42), and the percentage of patients demonstrating any degree of progression (50.9% vs 45.1%, p ​= ​0.20) were similar in those without and with standard modifiable risk factors, respectively. Conclusion: Patients who develop clinical coronary atherosclerosis without standard modifiable risk factors have similar rates of plaque progression to those with traditional risk factors.